FINANCIAL INCLUSION, CREDIT AND SAVINGS UNIONS AND POVERTY REDUCTION IN AYACUCHO, 2000-2020 - Grados Smith, Pedro (2022)
This article is based on my doctoral thesis supported in June 2022. The main objective is to demonstrate that the reduction of poverty in Peru in this century was related to financial inclusion mechanisms, recognizingthat GDP growth is the main factor that reduces poverty. Two econometric models are presented, the first at the aggregate level and the second at the specific level to analyze the main problems that are the main determinants of poverty reduction. The results of the first model showed financial inclusionas a determinant of the decrease in the use of poverty, measured as an indicator that concentrates penetration, availability, and banking. Likewise, the first model considers the growth of income per capita by department, among other variables. In the second model, data from the Credit and Savings Unions  -UNICAS- of Ayacucho were used to quantify the decrease in poverty in the districts where this public policy of financial inclusion was applied. The results of the second model show a decrease of five percentagepoints of poverty in the districts where the UNICAS are implemented.